Determination Analysis Of Capture Fisheries Resources Of Coastal Community Welfare In Eastern Indonesia Region:Revision Of Pandora Box Modell - Gigih Pratomo; Mega Rosdiana (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2018)
Eastern Indonesia Region has abundant marine resources and fisheries, especially in the Eastern Indonesia Region. Indonesia's marine potential is in contrast to its contribution to the economy which is classified as low and the limited employment opportunities for coastal communities. This study aims to identify the influence of capture fisheries resource determinants on the level of welfare of coastal communities in eastern Indonesia reigion through revision of Pandora box modell. This study uses a quantitative approach with secondary data obtained from literature studies and documentation. The variables used in this study are the Gross Regional Domestic Product, road infrastructure, electricity infrastructure, number of fishing vessel motors, human development index, and area of ??aquaculture. Data analysis techniques using multiple linear regression with panel data. The results show that road infrastructure and electricity infrastructure have a significant and positive effect on the level of community welfare in the Eastern Indonesia Region. Ship infrastructure has a significant negative effect on the welfare of the people of the Eastern Indonesia Region.